TAʿLĪM AL-LUGAH AL-ʿARABIYYAH LADA AL-TALĀMĪḎ MIN UṢŪL AL-ʿARAB - Nurul Aina (Jurnal Al-Maqoyis, 2020)
Students of Arab origins are children who first know the Arabic language from their families before learning in school. Therefore, their discourse when teaching Arabic is definitely better than other students who are not of Arab descent. The specificity of the discourse language of Arab individuals certainly affects their children in discourse. This is seen in acoustic signs in the speech. The reason is that the phonology of every language in the world has its own characteristics. We can see the characteristics of phonology in language from a variety of phonology in Arabic and other languages.Therefore, the researcher “Teaching Arabic to Student of Arab origins at Anak Sholeh Mandiri Primary School in Banjarmasin (audio study with the Software Praat ).To learn how to teach Arabic language and the characteristics of Students of Arab origins in the Islamic Primary School Anak Sholeh Mandiri in terms of phonetics. The researcher analyzes descriptive kualitatif and the software Praat ready program because it is one of the well-known ready-made program in Amsterdam and the best sound meter tools because it analyzes accurately and completely.The results of this research are:Teaching the Arabic language to Students of Arab origins at the Anak Sholeh Mandiri Islamic Primary School in Banjarmasin is organized into three departments, namely planning, implementation and evaluation. The planning of teaching the Arabic language to students of Arab origins in the Anak Sholeh Mandiri Islamic Elementary School in Banjarmasin is excellent, which consists of: education objectives, teaching materials, teaching activities, teaching methods, their sources and evaluation. And its implementation is very good, because its implementation is appropriate in most of the educational activities that are organized in stages to achieve the educational goals, and stages consisting of opening activities, basic activities and closing activities. As for evaluating it with an excellent degree, because it is evaluated by planning and organizing before the activities, that an evaluation is held four times in the middle, and the evaluation is made appropriate to all skills and is appropriate to the objectives of education and teaching materials. The exercises are varied.And the phonological characteristics of Arab students of Anak Sholeh Mandiri Primary School in Banjarmasin, analyzed by "Software Praat". The researcher writes the conclusion as follows: that the highest degree of the high degree of the vocabulary is the word ممرضة, the highest degree of the high degree of the vocabulary Pitch is the word طبيب, the highest degree of the high degree of intensity of the vocabulary is the word موظف, and that the high degree of duration The vocabulary that students of Arab descent is spoken about 1.500 - 2.110. And a high degree of pitch vocabulary that pupils of Arab origins pronounce around 440 Hz - 500Hz. The intensity of the vocabulary of the vocabulary that the students of Arab origins utter is about 79 dB - 81 dB. The duration of the female student is longer than the male student, the Pitch score of the male student is higher than that of the female student, and the degree of Intensity of the male student is higher than that of the female student.Based on the results of the research, the researcher concluded the research propositions, which are: First: If the alphabetical letters with the accusative or double action movement are either in the beginning or the last of the word, Pitch and Intensity are high. Second: If the alphabets are members of its outlet upper teeth and gums and put the lips rounded the Pitch and Intensity High. Third: If the alphabets are with intensity or with table moves the pitch and intensity are also high.